Posture Correction, Pain Reduction, and Improved Mobility Through Corrective Physiotherapy in Individual Patients with Scoliosis : Case Report - Anggita Nurul Ikshanty; Adnan Faris Naufal; Reza Arshad Yanuar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Adolescent Idiopathic Scoliosis (AIS) is the most common progressive musculoskeletal disorder among adolescents, characterized by a lateral curvature of the spine with an unknown cause. This condition often results in postural asymmetry, chronic low back pain, and reduced mobility. This case report involves a 17-year-old female high school student diagnosed with AIS, presenting with lower back pain and functional limitations. The physiotherapy intervention included three sessions over two weeks, utilizing Microwave Diathermy (MWD) as a physical modality, along with Schroth method and strengthening exercises. The outcomes demonstrated a reduction in pain intensity, improved muscle strength, increased spinal mobility, and enhanced thoracic expansion. Additionally, the patient showed an improvement in quality of life as measured by the Scoliosis Research Society-22 (SRS-22) questionnaire. These findings suggest that structured conservative physiotherapy, combining physical modalities and specific exercises, is effective in alleviating clinical symptoms, improving postural awareness, and supporting the functional well-being of AIS patients. This case highlights the importance of early and consistent physiotherapeutic intervention to manage symptoms and potentially slow curve progression.